2016
DOI: 10.1111/spol.12241
|View full text |Cite
|
Sign up to set email alerts
|

Networks for Welfare Provision: Getting a Grip on Processes of Social Exclusion by Evaluating Network Effectiveness

Abstract: It has been repeatedly stated that the topic of network effectiveness has often been neglected. This has led to a situation of ‘network euphoria’ amongst practitioners and policymakers with regard to the creation of networks as a means to (re‐)organize welfare provision. Starting from a case study of networks for welfare provision in two Belgian cities, this article focuses on the effectiveness of service delivering networks at the client level, which is understood as the contribution of the network in improvi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…In an analysis of the articles published in prominent journals between 2003 and 2017, we found 278 articles on SLBs. The abstracts of these articles suggested that only five of them mobilized relational dimensions in the analysis (De Corte, Verschuere, & De Bie, ; Maroulis, ; Nisar & Maroulis, ; Siciliano, ; Siciliano, ). Additionally, these articles only consider social relationships among peers and neglect bureaucrat–citizen relations.…”
Section: Social Network and Relationships: Approaching Interactive Imentioning
confidence: 99%
“…In an analysis of the articles published in prominent journals between 2003 and 2017, we found 278 articles on SLBs. The abstracts of these articles suggested that only five of them mobilized relational dimensions in the analysis (De Corte, Verschuere, & De Bie, ; Maroulis, ; Nisar & Maroulis, ; Siciliano, ; Siciliano, ). Additionally, these articles only consider social relationships among peers and neglect bureaucrat–citizen relations.…”
Section: Social Network and Relationships: Approaching Interactive Imentioning
confidence: 99%
“…In establishing these forums, managers should be attentive to the dynamic nature of networks and their evolving structural and functional characteristics. It is recommended that they adopt clear and enforceable rules and procedures to facilitate such networks and support their members in reaching collectively accepted solutions and ideas for innovation through the lead of nurse champions ( De Corte et al, 2017 ). Yet, as our findings revealed, structural solutions in the form of diverse network are not enough.…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
“…However, factors that affect one-to-one partnerships (role simultaneity, perceptions of service delivery, the influence of time), as well as supply and social structures, also affect network composition and may take on greater importance in a network setting. Just as organizational identity can be dynamic, so can networks, which has implications for contract specification and formalization (De Corte, Verschuere, & De Bie, 2017). Similarly, just as nonprofit roles can affect contracts on a dyadic level (e.g., nonprofit-public entity), so too can roles affect membership in and performance of networks.…”
Section: Nonprofit Roles and Network Participationmentioning
confidence: 99%